Perbandingan Bank Tanah dengan Manajemen Aset Negara Terkait Pertanahan - Situngkir, Roma Tua; Adhim, Nur (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
In the Land Sector, the Job Creation Law has issued regulations regarding the existence of a Land Bank in Indonesia. Based on article 1 paragraph (1) Government Regulation Number 64 of 2021 states that the Land Bank is a special agency (sui generis) formed by the central government which is given certain authority to regulate land. However, prior to the existence of the Land Bank Agency, there was the State Asset Management Institute, the State Asset Management Institute was motivated by the not fully optimal utilization of state assets related to idle state assets. The purpose of writing this journal is to review and analyze how comparisons to Land Banks and State Asset Management Institutions are related to land in Indonesia based on applicable laws. Normative juridical research approach method. The research procedure is descriptive qualitative analysis and the data source used is primary data through literature and statutory studies.The conclusions in this study, 1) the similarities between the Land Bank and the State Asset Management Institute 2) the differences between the Land Bank and the State Asset Management Institute.